Review of Tarphiomimus species of New Zealand (Coleoptera: Zopheridae). Issue 1 (2nd January 2017) - Makita, Shu; Leschen, Richard A. B.
ABSTRACT: The endemic New Zealand beetle genus Tarphiomimus Wollaston is revised with two new species described. A total of five species are included in the genus: Tarphiomimus indentatus Wollaston, 1873 ; T. wollastoni Sharp, 1882 ; T. triregius sp. nov.; T. miyakadoi sp. nov.; and Tarphiomimus undosus (Broun) comb. nov. which is transferred from the genus Pristoderus Hope. A single specimen from the Chatham Islands is very similar to T. triregius, but further study and material is needed to evaluate its species status. All Tarphiomimus are described and illustrated and a key to species is provided. http://zoobank.org/urn:lsid:zoobank.org:pub:842D49C4-C75E-458E-9897-C3045ABC9C80